A posição dos clíticos pronominais no português sob a perspectiva dos sistemas adaptativos complexos: um estudo diacrônico - Thaís Franco de Paula (2019)
This work presents a diachronic study on the syntax of pronominal clitic placement in the Portuguese Language, from the analysis of data collected in two textual genres: historical chronicle and grammar. We historized the standardization of the usage of clitics in Portuguese grammars from the sixteenth to the nineteenth century, compiled several works already conducted on the theme on which we worked throughout the outlined period of time for the study, and proposed an alternate explanation to the one given by the consulted treatises. Based both on a quantitative and qualitative methodology, theoretically supported by the Usage-Based Functional Linguistics, Sociolinguistics and Complex Adaptive Systems, we attempted to verify whether the current proclitic tendency of pronominal clitics in Brazilian Portuguese (henceforth PB) results from either a linguistic innovation that occurred in Brazilian lands or from a retention which here preserved the features of Classic Portuguese, which means admitting that the change in the order of pronominal clitics would have occurred in Portugal in the modern period. The analysis of the type of clause as a possible conditioner of pronominal clitic placement signaled the possibility that the phonological changes that occurred in European Portuguese (henceforth PE) have affected the morphology of the language, which found a way to solve the problem through syntax, restructuring the order of pronominal clitics. Our results confirm, then, both the nesting of the change and the hypothesis of the retention of proclitic tendency from the classic period of the Portuguese Language in PB.